IMPLEMENTASI SMART VILLAGE DALAM PERSPEKTIF ADMINISTRASI PUBLIK: STUDI KASUS DI KOTA SAMARINDA KALIMANTAN TIMUR - Linda Afriani; Adi Wijaya; Husni Fahrudin (LPPM STIH Awang Long, 2026)
The implementation of the Smart Village concept has evolved as a strategic approach to address regional challenges, including gaps in public services and technological access. This study aims to analyze the implementation of the Smart Village program in Samarinda City, East Kalimantan, from a public administration perspective using George C. Edward III’s policy implementation framework, which encompasses four variables: communication, resources, disposition, and bureaucratic structure. A qualitative descriptive approach was employed, focusing on case studies in Kelurahan Lempake and Kelurahan Pelita. Data were analyzed utilizing Miles and Huberman’s interactive model, consisting of data reduction, data display, and conclusion drawing. The results indicate that the application of Smart RT and SamaGov/Samagov in both urban villages has successfully enhanced service efficiency, accelerated administrative processes, and enabled a paperless system. Nonetheless, the implementation continues to face challenges, such as low digital literacy among the public (particularly the elderly), limited human resource capacity of village/neighborhood (RT) officials, centralized archival data management at the city government level, and the absence of real-time monitoring dashboards at the urban village level. This study concludes that strong administrative commitment and adaptive communication patterns serve as the key determining factors for the success of this digital transformation.